Transcutaneous Auricular Vagus Nerve Stimulation at 20 Hz Improves Depression-Like Behaviors and Down-Regulates the Hyperactivity of HPA Axis in Chronic Unpredictable Mild Stress Model Rats - Li, Shaoyuan; Wang, Yu; Gao, Guojian; Guo, Xiao; Zhang, Yue; Zhang, Zixuan; Wang, Yifei; Zhang, Jinling; Wang, Junying; Li, Liang; Yang, Yongsheng; Rong, Peijing (Frontiers in Neuroscience, 2020)
Transcutaneous auricular vagus nerve stimulation (taVNS) has gained growing interest as a non-invasive and non-pharmacologic treatment option in various neurological and psychiatric disorders. Animal experiments and clinical trials confirm that taVNS at the auricular concha region has beneficial effects on depression. However, stimulation frequencies are selected empirically, and there is no evidence showing that any frequency is superior to the others. This study explores antidepressant-like effects of three frequencies of taVNS on rats subjected to chronic unpredictable mild stress (CUMS). Sprague-Dawley rats were randomly divided into five groups, i.e., the control, CUMS, 5 Hz-taVNS, 20 Hz-taVNS, and 100 Hz-taVNS groups. The three different frequencies were administered during the 30-min taVNS procedure once a day for 28 consecutive days. Rats exposed to CUMS showed signs of depression-like behaviors, including reduction in sucrose preference and increased immobility time in forced swimming and open field tests as well as significant dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis as detected by plasma corticosterone and adrenocorticotropic hormone concentration. The 28 days’ taVNS sessions with three frequencies elicited quite different consequences. Although 20 Hz taVNS significantly reversed the depression-like behaviors and downregulated the hyperactivity of the HPA axis, neither 5 nor 100 Hz showed any antidepressant-like effect on CUMS-induced rat behavior. Based on these results, we propose that, out of the three frequencies for taVNS intervention on depression, 20 Hz may be the optimized frequency to have a better modulation effect on HPA axis function by activating the auricular vagus nerve.